2020
DOI: 10.3390/ijms21134807
|View full text |Cite
|
Sign up to set email alerts
|

Implications of SARS-CoV-2 Mutations for Genomic RNA Structure and Host microRNA Targeting

Abstract: The SARS-CoV-2 virus is a recently-emerged zoonotic pathogen already well adapted to transmission and replication in humans. Although the mutation rate is limited, recently introduced mutations in SARS-CoV-2 have the potential to alter viral fitness. In addition to amino acid changes, mutations could affect RNA secondary structure critical to viral life cycle, or interfere with sequences targeted by host miRNAs. We have analysed subsets of genomes from SARS-CoV-2 isolates from around the globe and show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
74
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(74 citation statements)
references
References 107 publications
0
74
0
Order By: Relevance
“…But there were some mutations, such as T85I in nsp2 and P323L in nsp12, found no significant impact on integral protein structure according to our results. However, their high frequency prompt us to further investigate whether they could affect virus characteristics via altering RNA second structure [20], protein stability [21] or partial structure [22]. For instance, experimental research reported that D614G in S could lead to virus infectivity increased by eliminating side-chain hydrogen bond which was only a tiny change in overall protein structure [23], and our data also showed small structural difference between D614G mutant and control (RMSD = 2.33 Å).…”
Section: Discussionmentioning
confidence: 62%
“…But there were some mutations, such as T85I in nsp2 and P323L in nsp12, found no significant impact on integral protein structure according to our results. However, their high frequency prompt us to further investigate whether they could affect virus characteristics via altering RNA second structure [20], protein stability [21] or partial structure [22]. For instance, experimental research reported that D614G in S could lead to virus infectivity increased by eliminating side-chain hydrogen bond which was only a tiny change in overall protein structure [23], and our data also showed small structural difference between D614G mutant and control (RMSD = 2.33 Å).…”
Section: Discussionmentioning
confidence: 62%
“…Several studies have predicted possible binding sites for miRNAs on the SARS-CoV-2 genome from the beginning of the COVID-19 pandemic [ [22] , [23] , [24] , [25] , [26] ]. Arisan et al (2020) identified seven miRNAs including miR-8066, miR-5197, miR-3611, miR-1307-3p, miR-3691-3p, miR-3934-3p, and miR-1468-5p, which bind to SARS-CoV-2 genome [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Arisan et al (2020) identified seven miRNAs including miR-8066, miR-5197, miR-3611, miR-1307-3p, miR-3691-3p, miR-3934-3p, and miR-1468-5p, which bind to SARS-CoV-2 genome [ 25 ]. In another study by D. McLellan et al (2020), ten microRNAs expressed in the SARS-CoV-2 target cells were filtered according to databases and published data and mutations within the binging sites of these miRNAs on the SARS-CoV-2 genome were investigated [ 26 ]. They identified eight mutations and hypothesized that these mutations might affect the host miRNA antiviral defenses.…”
Section: Discussionmentioning
confidence: 99%
“…Another study of a sequence analysis of SARS-CoV-2 genome has identified that out of 10, 3 targets have been lost. This includes miR 197-5p [65].…”
Section: Article Highlightsmentioning
confidence: 99%